Avaliação do uso de cinza de madeira e metacaulim na produção de tijolos leves de solo-cimento - Souza, Jônatas Macêdo de (2023)
Given the concern with the emission of greenhouse gases, companies in various economic sectors are using biomass as a fuel to generate thermal energy in boilers instead of the fossil fuels usually used. One of the biofuels used is wood chips, a small lignocellulosic material obtained from wood chopping. However, despite the environmental advantage of offsetting carbon dioxide (CO2) emissions, when burned, the material generates ash as a residue that, when not reused in agriculture as fertilizer or for composting, is sent to landfills or dumps, causing environmental impacts. Thus, there is a need for further studies on the physical and chemical properties of the ash so that new applications are thought of to promote a better destination for the residue. In view of the above, this research aimed to evaluate the influence of wood ash in conjunction with metakaolin - pozzolanic material - as a replacement for clay-silt soil (classified as A-6) in producing lightweight soil-cement bricks. In all, 7 formulations with 10% cement were produced, of which one was a reference (without substitutions), 3 with partial substitution of the soil by the contents of 5%, 10% and 20% of ash and 3 with the same contents of ash plus 5% of metakaolin replacing the soil. The bricks were cured for 7 days in a humid chamber. Then they were submitted to the compressive strength and water absorption tests at 7 and 28 days according to NBR 8492 and the durability test at 7 days according to NBR 13554. The samples with the best performance in the compressive strength test at 28 days, before and after the durability test, were submitted to microscopic characterization tests through X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) techniques. The tested bricks showed low density, less than 1.65 g/cm³ at 28 days, especially the sample with soil replacement by 20% ash and 5% of metakaolin with 1.22 g/cm³. As for the compressive strength at 28 days, except the formulation with soil substitution by 20% of the residue, all others showed results higher than 2 MPa, meeting the NBR 8491. Due to the high fines content in the soil (61.21% passing sieve No. 200), the average absorption of all compositions was above 20%. After being submitted to the durability test by immersion and drying, all formulations presented mass loss below the 7% indicated for soil type A-6 in NBR 13553. The microstructural characterization identified mineralogical phases of the products of the cementitious reactions as CSH and CASH, also confirmed by the microstructure images obtained in SEM. The results are promising and validate the use of ash with or without metakaolin to produce soilcement lightweight bricks.